Total Glucosides of Paeony Promote Intestinal Motility in Slow Transit Constipation Rats through Amelioration of Interstitial Cells of Cajal - Zhu, Feiye (PLoS One, 2016)
OBJECTIVES: Using an atropine-diphenoxylate-induced slow transit constipation (STC) model, this study explored the effects of the total glucosides of paeony (TGP) in the treatment of STC and the possible mechanisms. STUDY DESIGN: A prospective experimental animal study. METHODS: The constipation model was set up in rats with an oral gavage of atropine-diphenoxylate and then treated with the TGP. The volume and moisture content of the faeces were observed and the intestinal kinetic power was evaluated. Meanwhile, the colorimetric method and enzyme linked immunosorbent assay (ELISA) were employed to determine the changes of nitric oxide (NO), nitric oxide synthase (NOS), vasoative intestinal peptide (VIP) and the P substance (SP) in the serum, respectively. The protein expressions of c-kit and stem cell factor (SCF) were assessed by immunohistochemical analysis and western blot, respectively, and the mRNA level of c-kit was measured by a reverse transcription polymerase chain reaction (RT-PCR). RESULTS: The TGP attenuated STC responses in terms of an increase in the fecal volume and moisture content, an enhancement of intestinal transit rate and the reduction of NO, NOS and VIP in the serum. In addition, the c-kit, a labeling of interstitial cells of Cajal (ICC) increased at both protein and mRNA levels. SCF, which serves as a ligand of c-kit also increased at protein level. CONCLUSION: The analysis of our data indicated that the TGP could obviously attenuate STC through improving the function of ICC and blocking the inhibitory neurotransmitters such as NO, NOS and VIP.